Evaluation of COVID-19 pandemic management in Türkiye - Kartoglu, Umit; Pala, Kayihan (Frontiers in Public Health, 2023)
Three years since the first cases were identified and two years since an effective vaccine was developed, COVID-19 continues to claim lives and impact people’s wellbeing, both socially and economically. While the world has been waiting for its leaders to come together forming a collective response to end the pandemic, we still have not seen a multisectoral response, nor any whole-of-society approach. Like many other countries, Türkiye was also caught unprepared. This was exacerbated by the unsuccessful management of the pandemic by the authorities. The reasoning and/or scientific explanations for enforcing or lifting public health measures have never shared with the public. Throughout the pandemic, no epidemiological details have been released on cases and deaths, other than the numbers of these two measures. Civil society organizations, professional associations, and the public in general have been kept out from policy formulation and decision making. As a result, community engagement has never been properly put into practice. In this paper, we analyzed Türkiye’s pandemic management response through the continuum of the response cycle to emergencies: prevention, preparedness, readiness, response, and recovery.